Atropine Differentially Modulates ECM Production by Ocular Fibroblasts, and Its Ocular Surface Toxicity Is Blunted by Colostrum - Martina Cristaldi; Melania Olivieri; Salvatore Pezzino; Giorgia Spampinato; Gabriella Lupo; Carmelina Daniela Anfuso; Dario Rusciano (Biomedicines, 2020)
Background: The etiology and the mechanism behind atropine treatment of progressive myopia are still poorly understood. Our study addressed the role of scleral and choroidal fibroblasts in myopia development and atropine function. Methods: Fibroblasts treated in vitro with atropine or 7-methylxanthine were tested for ECM production by Western blotting. Corneal epithelial cells were treated with atropine in the presence or absence of colostrum or fucosyl-lactose, and cell survival was evaluated by the MTT metabolic test. Results: Atropine and 7-methyl-xanthine stimulated collagen I and fibronectin production in scleral fibroblasts, while they inhibited their production in choroidal fibroblasts. Four days of treatment with atropine of corneal epithelial cells significantly decreased cell viability, which could be prevented by the presence of colostrum or fucosyl-lactose. Conclusions: Our results show that atropine may function in different ways in different eye districts, strengthening the scleral ECM and increasing permeability in the choroid. The finding that colostrum or fucosyl-lactose attenuate the corneal epithelial toxicity after long-term atropine treatment suggests the possibility that both compounds can efficiently blunt its toxicity in children subjected to chronic atropine treatment.